The Effect of Teenage Passengers on Simulated Risky Driving Among Teenagers: A Randomized Trial - Simons-Morton, Bruce G.; Bingham, C. Raymond; Li, Kaigang; Zhu, Chunming; Buckley, Lisa; Falk, Emily B.; Shope, Jean Thatcher (Frontiers in Psychology, 2019)
Teenage passengers might influence risky driving, particularly in certain mental states. Notably, social exclusion could increase social conformity. Two studies examined simulated intersection management among young drivers after a social exclusion activity (Cyberball). In Study 1 (112 males (mean = 17.3 years), risky driving was significantly greater among excluded males driving with a risk-accepting vs passive passenger; no effect of social exclusion. In Study 2 (115 females (mean = 17.1 years), risky driving was significantly greater among excluded females driving with a risk-accepting vs a passive passenger, and greater among those included (fair play) vs excluded when driving with a risk-accepting passenger. Risky driving behavior among male and female teenagers may be influenced uniquely by passenger norms and social exclusioninclusion.